MENGEKSPLORASI TANGGUNG JAWAB DAN KREATIVITAS ILMIAH PESERTA DIDIK MELALUI CREATIVE RESPONSIBILITY BASED LEARNING - Muhammad Feyzar Rif'at; Mustika Wati; Suyidno Suyidno (Journal of Banua Science Education, 2021)
Scientific responsibility and creativity are part of the main competencies in the era of the industrial revolution 4.0, but they are not trained in schools. Therefore, the purpose of this study is to analyze the effectiveness of Creative Responsibility Based Learning in exploring the responsibility and scientific creativity of students. This research is part of research and development with the ADDIE model, namely at the implementation and evaluation stages. The research trial used one group pre-test and post-test on 27 students of class XI MIPA 2 MAN 2 Banjarmasin. Data collection instruments consist of responsibility observation sheets with indicators of participating, respecting others, cooperation, leading, and expressing opinions; as well as a scientific creativity test which includes indicators of finding problems, imagining scientifically, solving problems creatively, and designing products creatively. The results showed that the responsibility of the students at each meeting was in good criteria. In addition, the scientific creativity N-gain was 0.34 in the medium criteria. Thus, CRBL is effectively used to explore the responsibility and scientific creativity of students.  Kata kunci: creative responsibility based learning, scientific creativity, responsibility AbstrakTanggung jawab dan kreativitas ilmiah merupakan bagian dari kompetensi utama di era revolusi industri 4.0, namun kurang dilatihkan di sekolah. O